Analisis Tingkat Minat Beli Konsumen pada Masa Pandemi Covid-19 (Studi Pada Konsumen Pasar Buku Palasari Kota Bandung) - Dinanti, Dhica (Asosiasi Ahli Administrasi Indonesia, 2021)
Bandung City has a traditional book market established since the 1980s, it called Pasar Buku Palasari. Until 2019, there are around 200 stall at Pasar Buku Palasari. However, entering 2020 there is an invisible disaster that attack the entire world. The disaster is Covid-19 Pandemic, which until now the cases is still increasing. Then, what about the consumers of Pasar Buku Palasari? Has this pandemic affercted their buying interest? The author is interestend by doing this research with the aim is knowing the level of consumer buying interest in Pasar Buku Palasari during the Covid-19 Pandemic. The method used in this research is quantitative descriptive method. The data collection technique used by distributing online quisionnare to 114 respondents. When the data from quisionnare has been collected, data processing is used application that name IBM Statistic SPSS 25. In the result, it is found that the dominant respondent comes from young people with the profession as a students. The average for all question item is bigger than the average of standard deviation, this indicates that the results obtained are sufficient. The average for all question item is 3.09625, which means that consumer buying interest in the Pasar Buku Palasari during the Covid-19 Pandemic is quite high.